Prevalence and risk factors of caseous lymphadenitis in goats from selected farms in Selangor, Malaysia - Ismail, Muhamad Shahriman; Ramanoon, Siti Zubaidah; Ong, Bee Lee (2012)
Caseous Lymphadenitis (CLA) is not well-studied in Malaysia despite the fact that the disease is common in goats. Therefore, this study was conducted to determine the prevalence and the risk factors for CLA in goats from eight selected farms in Selangor, Malaysia. In total, 159 serum samples were collected once via jugular venipuncture and subjected to the agar gel immune-diffusion (AGID) test to estimate the prevalence of CLA. Information on the potential risk factors for CLA at the animal and farm levels was collected through a questionnaire. The prevalence of CLA was estimated at 28% in goats and 75% in farms in Selangor. Goats with body condition score (BCS) of lower than 2, older than one year old, and female were significantly associated with higher prevalence of CLA (P<0.05). Eighty-eight percent (7/8) of farms were under intensive system, 63% (5/8) had less than three workers, 63% (5/8) with history of CLA, 50% (4/8) were at least 6 years old, 50% (4/8) had more than 150 animals; 50% had male:female of 1:11-20, 50% had isolation pens, 13% (1/8) had sharp objects in pens, all had perimeter fence, 50% practised farm quarantine, 38% (3/8) had added new animals, 25% (2/8) imported new animals, 13% (1/8) had foot-dip, 75% (6/8) had treated cases of CLA ,75% had deworming programmes, and none practiced CLA vaccination programme in their farms. In conclusion, the high prevalence of CLA in goats from the selected farms in Selangor that could be due to poor management practices, lack of biosecurity measures and vaccination programmes. Therefore, these factors should be taken into consideration when formulating programmes for effective prevention and control of CLA in goats.